Desenvolvimentos de uma genealogia da governamentalidade : a noção de parresia entre a ética e a política - Santos, Alexandre Gomes dos (2017)
Our aim with the present research is a "genealogy of governmentality" based on the investigations undertaken by Michel Foucault in the last years of the Collège de France, when notions of "spirituality", "ascesis" and "parresía" are used to articulate politics and ethics around the government of self and others, tracing the development of the "self-arts," elements of a Greek and Roman ethos, for governing arts of self and others, this through the logical chain "relations of power / governmentality / government of self and others / relation of self to you ". In addition, to point out the ethical consequences that such genealogy brings to our present, especially regarding the theme "freedom" as a possible thematic field for which we are taken from the Foucaultian studies around the aesthetics of existence.